(untitled) (Revista Cocar, 2023)
Este artigo apresenta a defesa do transporte público escolar à garantia do acesso às escolas da zona rural de Porto Velho (RO). O problema é: como a falta do transporte público escolar impactou nas matrículas dos alunos das escolas rurais e ao mesmo tempo pode impactar no espaço urbano? A metodologia é de abordagem qualitativa; com procedimento bibliográfico e documental. Como resultado, apresenta a resolução orientada pela Carta de Brasília, de modo a planejar um instrumento de tutela capaz de eliminar as desigualdades entre as escolas do campo e da cidade. Palavras-chave: Acesso à Educação. Escolas rurais. Transporte público escolar. Abstract This paper presents the defense of public school transportation to guarantee access to schools in the rural area of Porto Velho, in the state of Rondônia. The problem is how the deficit of public school transportation has impacted student enrollment in rural schools, and at the same time how this could affect the urban space? The methodology is a qualitative approach; with bibliographic and documentary procedure. As a result, it presents the resolution guided by the Brasilia Charter and the use of information technologies, in order to plan a tutelage instrument capable of eliminating inequalities between rural and urban schools Keywords: Access to education. Rural schools. Public school transportation.